Characterization of a diamond ground Y-TZP and reversion of the tetragonal to monoclinic transformation - Candido, L. M. [UNESP]; Fais, L. M.G. [UNESP]; Ferreira, E. B.; Antonio, S. G. [UNESP]; Pinelli, L. A.P. [UNESP] (Operative Dentistry, 2017)
Purpose: To characterize the surface of an yttria-stabilized zirconia (Y-TZP) ceramic after diamond grinding in terms of its crystalline phase, morphology, mean roughness (Ra), and wettability as well as to determine a thermal treatment to reverse the resulting tetragonal to monoclinic (t-m) transformation. Methods and Materials: Y-TZP specimens were distributed into different groups according to the actions (or no action) of grinding and irrigation. Grinding was accomplished using a diamond stone at a low speed. The samples were characterized by x-ray diffraction (XRD), scanning electron microscopy, goniometry, and profilometry. In situ high-temperature XRD was used to determine an annealing temperature to reverse the t-m transformation. Ra was submitted to the Kruskal-Wallis test, followed by the Dunn test (α=0.05). The volume fraction of the monoclinic phase and contact angle were submitted to one-way analysis of variance, followed by the Tukey test (α=0.05). Results: Monoclinic zirconia was observed on the surface of samples after dry and wet grinding with a diamond stone. The volume fraction of the monoclinic phase was smaller on the dry ground samples (3.6%±0.3%) than on the wet ground samples (5.6%±0.3%). Hightemperature XRD showed reversion of the t-m phase transformation, which started at 7008C and completed at 8008C in a conventional oven. Conclusions: Grinding with a diamond stone partially transformed the crystalline phase on the surface of a Y-TZP ceramic from tetragonal to monoclinic zirconia while simultaneously increasing the surface roughness and wettability. The t-m transformation could be reversed by heat treatment at 800°C or 900°C for 60 minutes or 1000°C for 30 minutes.